Roles of increased glycemic variability, GLP-1 and glucagon in hypoglycaemia after Roux-en-Y gastric bypass. - Tharakan,G; Behary,P; Wewer,Albrechtsen NJ; Chahal,H; Kenkre,J; Miras,AD; Ahmed,AR; Holst,JJ; Bloom,SR; Tan,TMM (European Journal of Endocrinology, 2017)
Objective Roux-en-Y Gastric Bypass (RYGB) surgery is currently the most effective treatment for diabetes and obesity. An increasingly recognized complication of RYGB surgery is postprandial hypoglycemia (PPH). The pathophysiology of PPH remains unclear with multiple mechanisms suggested including nesidioblastosis, altered insulin clearance and increased glucagon-like-1 peptide (GLP-1) secretion. Whilst many PPH patients respond to dietary modification, some have severely disabling symptoms. Multiple treatments have been trialled ranging from acarbose, to both GLP-1 agonists and antagonists, even to reversal of RYGB. A greater understanding of the pathophysiology of PPH could guide the development of new therapeutic strategies. Methods We studied a cohort of PPH patients at the Imperial Weight Center. We performed continuous glucose monitoring to characterize their altered glycemic variability. We also performed a mixed meal test (MMT) and measured gut hormone concentrations. Results We found increased glycemic variability in our cohort of PPH patients, specifically a higher Mean Amplitude Glucose Excursion (MAGE) score of 4.9. We also demonstrated significantly greater and earlier increases in insulin and GLP-1 concentration in patients who had hypoglycemia in response to an MMT (MMT Hypo) relative to those that did not (MMT Non-Hypo). There was a significantly increased glucagon secretion in the MMT Hypo group versus the Non-hypo group. No significant differences in oxyntomodulin, GIP or peptide YY secretion were seen between these two groups. Conclusion An early peak in GLP-1 and glucagon, due to post-operative L-cell hypertrophy and aberrant processing of proglucagon, may trigger an exaggerated insulinotropic response to eating in patients with PPH.